Closed Reduction of Pediatric Distal Radial Fractures and Epiphyseal Separations. Issue 4 (October 2020) - Gohel, Shivani; Baldwin, Keith D.; Hill, Jaclyn F.
Abstract : Background: Sedated, closed reduction of a displaced distal radial fracture followed by cast immobilization is indicated in cases of unacceptable alignment on post-splint imaging. The aim of this procedure is to obtain acceptable reduction and cast immobilization for fracture-healing. Description: The patient is positioned supine with the injured arm on the image intensifier. Adequate sedation is achieved with conscious sedation, general anesthesia, or regional anesthesia (hematoma block). The radial or ulnar translation is corrected with in-line traction. The wrist is typically hyperdorsiflexed, and traction is applied to the distal fragment. The distal fragment is then walked up and over as axial traction is applied and the wrist is brought from extension to flexion. The reduced wrist is held in a position of gentle flexion and slight ulnar deviation, and post-reduction fluoroscopy in anteroposterior and lateral views is obtained. A long-arm cast is applied by first applying a short-arm cast and a 3-point mold. Minimal cast padding is utilized to obtain the optimal "cast index." The wrist is re-imaged on the fluoroscopy device to obtain anteroposterior and lateral views. Alternatives: Alternative treatments include cast immobilization in situ, closed reduction and percutaneous pinning, and open reduction and internal fixation. Rationale: Closed reduction and cast immobilization is a low-risk procedure that has a high rate of union with acceptable alignment without the risk of an additional surgical procedure. Expected Outcomes: The long-arm cast is maintained for 6 weeks, and radiographs are obtained at 1 and at 2 weeks postoperatively to confirm maintained alignment. It is advisable to instruct the patient not to put anything down the cast because this can result in skin breakdown. Additionally, care must be taken on removal of the cast. Cast saws should be kept sharp and be replaced frequently. There are commercially available "zip sticks" and other such devices to prevent cast-saw burns that should be utilized if cast technicians or residents are assisting in the removal. Following removal of the cast, we recommend wrist-motion exercises be performed 3 times daily. If the fracture line is clearly visible on radiographs, a removable wrist splint is utilized for another 2 to 4 weeks. A full return to activity is expected at 3 months. Some residual deformity is acceptable if the remodeling capacity is excellent at the distal aspect of the radius. However, the tolerance for malreduction decreases as the patient ages, if the deformity worsens, or if there is a deformity further from the physis. Important Tips: Particular attention should be given to the median nerve sensory component. The thumb, index, and long fingers are assessed for sensation and compared with the 2 ulnar digits. Acute carpal tunnel syndrome is possible in children who have distal radial fractures. Waterproof cast padding is not recommended in cases in which a closed reduction is performed because such padding does not provide good protection to the skin with adequate cast molding. After reduction is obtained, no additional traction should be applied. If an assistant applies traction with the wrist in extension, reduction can be lost, so it is preferred to maintain the wrist in slight flexion while placing the cast. Although it is beneficial to hold the fracture in the cotton-loader position, this position should not be exaggerated because this position can cause excessive pressure on the carpal tunnel. The median nerve passes through the carpal tunnel and is often at risk because of hematoma formation as a result of a distal radial fracture. A cast index of 0.8 or more has been found to have an increased risk of failure of closed treatment. The cast index is the ratio of sagittal (measured on a lateral view) to coronal (measured on an anteroposterior view) width from the inside edges of the cast at the fracture site. Keeping cast saw blades sharp, using saws attached to vacuum devices, and cooling the blade while in use can prevent cast-saw burns. Zip sticks can be utilized to protect the skin but can sometimes be difficult to get under the cast. It is important to remember that swelling will occur following fracture reduction. The cast should not be wrapped tightly. Consideration should be given to bivalving the cast at the time of reduction and overwrapping after a few days when acute swelling has improved. Vigilance for growth arrest is necessary in patients with fractures of the distal aspect of the radius. This can occur in up to 4% to 5% of cases and is more common with reduction, particularly late reduction. Radiographic screening 6 to 12 months after the injury can help identify an early arrest.